Developing moral education through service learning: Indonesia higher education context / Obby Taufik Hidayat and Vishalache Balakrishnan - Hidayat, Obby Taufik; Balakrishnan, Vishalache (Universiti Teknologi MARA, 2024)
Moral Education (ME) is essential for establishing desirable personality characteristics in a multicultural society. However, many graduates in Indonesia still show moral decadence due to low educational standards, and in particular, universities still do not optimize ME. Therefore, this study aims to develop ME through service learning through Kuliah Kerja Nyata (KKN) or the subject of community service for university students. The case study design reveals the depth and richness of information on the service learning program in Indonesia, including students and lecturers in the multicultural community. Data collection would entail recording students working on service-learning projects and thematic analysis. The results show that service learning has successfully promoted social responsibility, solidarity, and tolerance among students. The effectiveness of the lecturer's innovative pedagogy can be seen in the students' awareness and behaviour. This research offers recommendations and insights that should be utilized to lessen moral issues in youth.